2020
DOI: 10.1177/1526602820971830
|View full text |Cite
|
Sign up to set email alerts
|

Open Conversion After Endovascular Aneurysm Sealing: Technical Features and Clinical Outcomes in 44 Patients

Abstract: Purpose To evaluate the technical features and clinical results after open conversion for complications following endovascular aneurysm sealing (EVAS). Materials and Methods From July 2013 to February 2020, 44 patients (mean age 72±8 years; 36 men) underwent an open conversion due to EVAS complications in a single center. Data were collected on patient characteristics, reasons for conversion, characteristics and duration of the procedure, condition of the polymer, blood loss, time in the intensive care unit (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In January 2019, unforeseen complications led to the stop of unrestricted sales and commercial use of the device. The main reason for this being a higher than anticipated migration and endoleak rate 25 leading to complex open conversions. However, sac-sealing devices might still have a future as primary procedures or as adjuncts for reintervention in complications, such as type III endoleak.…”
Section: Discussionmentioning
confidence: 98%
“…In January 2019, unforeseen complications led to the stop of unrestricted sales and commercial use of the device. The main reason for this being a higher than anticipated migration and endoleak rate 25 leading to complex open conversions. However, sac-sealing devices might still have a future as primary procedures or as adjuncts for reintervention in complications, such as type III endoleak.…”
Section: Discussionmentioning
confidence: 98%
“…13 A further contemporary series of 44 explantations for various indications also identified significantly poorer outcomes in urgent or emergency cases. 14 Therefore, these data would support early explantation of failing devices in fit patients in an elective setting.…”
Section: Management Of Device Migration and Endoleakmentioning
confidence: 90%
“…For patients operated urgently, our 30-day mortality rate was significantly higher than elective patients (40% vs 7.1%, p=0.038). The significantly increased mortality associated with nonelective conversions highlights the need for active surveillance 27 and management at high-volume aortic referral centers. 28 Long-term results of the EVAR 1 trial have shown worse mortality in the EVAR group beyond 8 years, primarily the result of increased rates of secondary aneurysm sac rupture.…”
Section: Discussionmentioning
confidence: 99%
“…For patients operated urgently, our 30-day mortality rate was significantly higher than elective patients (40% vs 7.1%, p=0.038). The significantly increased mortality associated with nonelective conversions highlights the need for active surveillance 27 and management at high-volume aortic referral centers. 28…”
Section: Discussionmentioning
confidence: 99%